PERAN TENAGA KEPENDIDIKAN DALAM MENINGKATKAN MUTU LAYANAN SISWA - Saima Sonang Pohan; Zaini Dahlan, Nurmarito Rambe, Taufik Hidayat (CV. ADIBA AISHA AMIRA, 2024)
This research aims to identify and analyze the role of educational energy in improving student services. Educational staff, including teachers, administrative staff, counselors and other support staff, have an important role in providing services that influence student development and welfare. These services are an important aspect of a quality education system. This research was conducted at the Darussalam Parmeraan Islamic Boarding School Tsanawiyah Madrasah. The method used in this research is library research. The data collection techniques used in this research are documentation techniques, books and newspapers. The results of this research state that student services at the madrasa are running well. This madrasa is able to compete with other madrasas and at the tertiary level.